2017
DOI: 10.1016/j.antiviral.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Cellular protein GLTSCR2: A valuable target for the development of broad-spectrum antivirals

Abstract: Viral infection induces translocation of the nucleolar protein GLTSCR2 from the nucleus to the cytoplasm, resulting in attenuation of the type I interferon IFN-β. Addressing the role of GLTSCR2 in viral replication, we detect that knocking down GLTSCR2 by shRNAs results in significant suppression of viral replication in mammalian and chicken cells. Injection of chicken embryo with the GLTSCR2-specific shRNA-1370 simultaneously or 24 h prior to infection with Newcastle disease virus (NDV) substantially reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…For each inoculation, a mixture of HHT (Aladdin, 98% purity) and NDV (50 plaque-forming units (PFU)) or AIV (500 PFU) was injected into the allantoic cavity of specific pathogen-free (SPF) chicken eggs. Eggs were incubated for different times, and allantoic fluid was harvested to measure viral yields, as described in our previous report [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…For each inoculation, a mixture of HHT (Aladdin, 98% purity) and NDV (50 plaque-forming units (PFU)) or AIV (500 PFU) was injected into the allantoic cavity of specific pathogen-free (SPF) chicken eggs. Eggs were incubated for different times, and allantoic fluid was harvested to measure viral yields, as described in our previous report [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study revealed that NOP53-derived recombinant protein N4-T, forming α-helical dimer, promotes replication of seven different viruses via suppression of the IFN-β antiviral response 44 . In consideration of the relationship between NOP53 redistribution and viral replication priority, N4-T protein was employed in this study.…”
Section: Nop53-derived Recombinant Protein Attenuates P-eif2α In Cellmentioning
confidence: 99%
“…N4-T, in which Tat (GGSRYGRKKRRQRRR) was conjugated at the C-terminal of N4, was expressed and purified as described previously 44 . Cells treated with N4-T were harvested for plaque formation assay or Western blotting analysis.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…In RNA interference (RNAi), short interfering RNA molecules or short hairpin RNA (shRNA) targeting speci c mRNA leads to degradation of mRNA and inhibition of gene expression [6][7]. RNAi targeting viral genes is an effective way to prevent cells from virus infection, and has been shown to mediate genetic suppression of many human and animal pathogenic coronaviruses [8,9,10]. Heptad repeat (HR) regions are highly conserved motifs located in spike glycoprotein of enveloped viruses.…”
Section: Introductionmentioning
confidence: 99%